Prevalence of antibiotic-resistant Escherichia coli isolates from healthy chicken droppings - Ali M. Hussein; Ali J. Muhialdin; Rahman K. Faraj (PLoS ONE, 2025)
Background The increasing emergence of antimicrobial-resistant (AMR) Escherichia coli in poultry represents significant public health concern due to the risk of zoonotic transmission via the food chain. This study investigates the prevalence and resistance patterns of E. coli isolated from healthy broiler and indigenous chickens in Kifri City, Kurdistan Region, Iraq. Methods A total of 200 cloacal swab samples were collected from healthy chickens (100 broilers and 100 indigenous). Standard bacteriological methods were used for E. coli isolation, followed by antimicrobial susceptibility testing against ten antibiotics using the Kirby-Bauer disc diffusion method. Additionally, molecular detection of resistance genes was performed via PCR. Results The overall isolation rate of E. coli was 60%. Broiler isolates exhibited significantly higher resistance rates, including 100% resistance to ciprofloxacin and enrofloxacin, and >90% resistance to amoxicillin, amoxicillin-clavulanate, norfloxacin, and nitrofurantoin. In contrast, indigenous chicken isolates showed lower resistance, with the highest rates seen for amoxicillin-clavulanate (90%) and nitrofurantoin (85%). PCR analysis identified the presence of key resistance genes including blaTEM , qnrS , and sul1 among multidrug-resistant isolates. Statistically significant differences (p < 0.05) were observed in resistance profiles between broiler and indigenous groups. Conclusion The high prevalence of multidrug-resistant E. coli in broiler chickens underscores the urgent need for stricter antibiotic stewardship in poultry farming. The findings support Sustainable Development Goals (SDGs) 3 (Good Health and Well-being), 12 (Responsible Consumption and Production), and 15 (Life on Land) by promoting antimicrobial surveillance and sustainable livestock management.